Undifferentiated carcinoma with osteoclast-like giant cells of the pancreas: a narrative review - Wu, Haoxiang (Frontiers in Oncology, 2024)
Undifferentiated carcinoma with osteoclast-like giant cells of the pancreas (UCOGCP) is a rare pancreatic tumor that accounts for less than 1% of all pancreatic malignancies. The characteristic pathological manifestation of UCOGCP is the presence of osteoclast-like giant cells (OGCs) distributed among pleomorphic undifferentiated tumor cells. UCOGCP can occur either alone or in association with other types of pancreatic tumors. At present, there is no unified consensus or guideline for the diagnosis and treatment of UCOGCP, and most of the literature are individual case reports. With the accumulation in the number of clinical cases and the development of precision medicine technology, the understanding of UCOGCP is also deepening. Researchers have begun to recognize that UCOGCP is a pancreatic tumor with distinctive clinical and molecular characteristics. In this review, we focus on the latest research status and future exploration directions in the diagnosis, treatment, and prognosis of UCOGCP.